Book Review. Issue 2 (1st December 2021) - Unknown
Abstract : McKee Hurwitz, Heather. 2020. Are We the 99%? The Occupy Movement, Feminism and Intersectionality. Philadelphia, PA: Temple University Press. 208 pp, index. EAN: 978-1-4399-2021-3 (hardback), 99.50; EAN: 978-1-4399-2022-0 (paperback), 25.95.